The relationship between socioeconomic status and childhood overweight/obesity is linked through paternal obesity and dietary intake: a cross-sectional study in Chongqing, China - Jingyu Chen; Shunqing Luo; Xiaohua Liang; Yetao Luo; Rina Li (Komiyama Printing Co. Ltd, 2021)
Abstract Background The prevalence of obesity and overweight in childhood has increased dramatically over the past decades globally. Thus, the risk factors of overweight and obesity in children and adolescents must be studied. Objectives This study aimed to reveal the prevalence of childhood obesity and examine the relationship between socioeconomic status (SES) and z-body mass index (z-BMI) via parental obesity and dietary intake using path analysis. Methods Stratified cluster sampling was used to select 17,007 participants aged 6-12 years on two avenues per region in urban, suburban, and rural areas. Path analysis was conducted to examine the mediators between SES and z-BMI. Results The prevalence rates of overweight and obesity were 13.36% and 8.60%, respectively, and were positively correlated with the father's education level, family income, a birth weight > 3000g, a parental obesity history, vegetable intake and red meat intake (all P < 0.05). Four mediators (paternal obesity history, red meat intake, vegetable intake, and nutritional supplements) were observed, and the four path analyses were significant (all P < 0.05). The adjusted total effects on z-BMI were significant for income (βTot = 0.03; P < 0.01), father's education (βTot = 0.05; P < 0.001), and region (βTot = 0.11; P<0.001), and the total mediation effects were 20.69%, 16.67%, and 5.36%, respectively. All the variables accounted for 12.60% of the z-BMI variance. Conclusions The prevalence of overweight/obesity in children was notable, and the relationship between SES and z-BMI was mediated by paternal obesity history and dietary intake.